INNOVATIVENESS OF EUROPEAN REGIONAL SPACE: CONVERGENCE OR DIVERGENCE? - Tomasz Kijek; Anna Matras-Bolibok (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the article is to assess the convergence of innovativeness in European regions at the NUTS-2 level. In the first part of the work, the concept of region’s innovativeness is defined and methods of its measurement are presented. Next, the conditions and determinants of convergence/divergence of innovativeness in the regional area are discussed. The theoretical part of the paper suggests that the issue of convergence in the field of innovativeness is a significant, but relatively poorly explored, research area in economic literature. The empirical part of the article presents the results of the study of sigma and gamma convergence of innovativeness in a group of European regions. The research sample consists of 220 regions from 22 European Union countries, as well as Norway, Serbia and Switzerland. The obtained results indicate the occurrence of sigma divergence processes and the lack of gamma convergence processes.